A revised interpretation of the Pennsylvanian flexible crinoid Zenocrinus zeus (Echinodermata). (27th June 2016) - Peter, Mark E.
Abstract: Moore and Strimple described the Morrowan (Lower Pennsylvanian, Bashkirian) crinoid Zenocrinus zeus, and noted significant differences in the number and arrangement of plates in the posterior interray between the holotype and the paratype, the only known specimens. A reexamination of the type specimens allowed for a reconciliation of these discrepancies. The new interpretation of Z. zeus necessitates a revision of the diagnosis, and a new plate diagram is proposed. Additional morphological features of the species are described, including the presence of a generating columnal between the column proxistele and mesistele, and a ratcheting profile for the exterior surfaces of calyx ray plates.